2020
DOI: 10.1101/2020.02.01.926303
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Layer-dependent multiplicative effects of spatial attention on contrast responses in human early visual cortex

Abstract: Attention mechanisms at different cortical layers of human visual cortex remain poorly understood. Using submillimeter-resolution fMRI at 7T, we investigated the effects of top-down spatial attention on the contrast responses across different cortical depths in human early visual cortex. Gradient echo (GE) T2* weighted BOLD signal showed an additive effect of attention on contrast responses across cortical depths. Compared to the middle cortical depth, attention modulation was stronger in the superficial and d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 73 publications
(79 reference statements)
0
6
0
Order By: Relevance
“…I re-ran the main analyses of colorfulness and sharpness with a version of the model with Rmax reduced by 25% ( Figure 8A, Rmax=22.5; this is consistent with the attentional effect on fMRI BOLD response (Buracas & Boynton, 2007;Gandhi et al, 1999;Guo et al, 2020); the relation of BOLD contrast response to perceptual contrast is not a straightforward equivalence, however). This is a significant reduction that produces psychophysical effects in a similar range to what has been observed in numerous studies, reducing sensitivity by around 20% (Fig.8B,C), depending on the default sensitivity of each mechanism, but I did not try to fit the reduction to any particular dataset (see (Carrasco et al, 2000;Lee et al, 1997) for similar effects, and many other effects of similar magnitude reviewed in (Carrasco, 2011)).…”
Section: Attentionmentioning
confidence: 56%
See 1 more Smart Citation
“…I re-ran the main analyses of colorfulness and sharpness with a version of the model with Rmax reduced by 25% ( Figure 8A, Rmax=22.5; this is consistent with the attentional effect on fMRI BOLD response (Buracas & Boynton, 2007;Gandhi et al, 1999;Guo et al, 2020); the relation of BOLD contrast response to perceptual contrast is not a straightforward equivalence, however). This is a significant reduction that produces psychophysical effects in a similar range to what has been observed in numerous studies, reducing sensitivity by around 20% (Fig.8B,C), depending on the default sensitivity of each mechanism, but I did not try to fit the reduction to any particular dataset (see (Carrasco et al, 2000;Lee et al, 1997) for similar effects, and many other effects of similar magnitude reviewed in (Carrasco, 2011)).…”
Section: Attentionmentioning
confidence: 56%
“…The target data on which the model is constructed and tested were all collected under conditions where the target stimulus was the sole focus of the observer's spatial attention. (Bressler et al, 2013;Buracas & Boynton, 2007;Guo et al, 2020;Herrmann et al, 2009;Reynolds & Heeger, 2009); so, withdrawal of spatial attention means reduced contrast sensitivity, reduced perceived contrast (but see (Schneider & Komlos, 2008)), and attenuated neural response. A crude implementation of this enhancement (or of its withdrawal) in the model would be to vary the amplitude (Rmax in Eq.9) of the contrast response function.…”
Section: Attentionmentioning
confidence: 99%
“…Beyond the spatial separation of perceived and mentally rotated contents, the laminar organization of feedforward and feedback information may also facilitate interactions between these signals. Processing bottom-up and top-down signals in close physical proximity on the cortical surface optimizes cross-talk that is essential for a large set of cognitive functions such as figure-ground segregation 16,34 , surround suppression 35 , visual attention [17][18][19] and visual short-term memory 12,14,36 . In fact, predictive coding accounts suggest that a multitude of brain processes depend on such interactions 37,38,39 , rendering the laminar separation of feedforward and feedback information a candidate for an implementation strategy for various other brain functions.…”
Section: Discussionmentioning
confidence: 99%
“…Feedforward projections terminate in the middle layer, while feedback connections terminate in superficial and deep layers [6][7][8][9][10][11] . Studies of working memory and attention demonstrated the functional relevance of this layer-specific separation [12][13][14][15][16][17][18][19] . However, these studies measured the retention or amplification of the very stimuli previously represented in V1 or estimated perception signal not concurrently but in a separate task.…”
Section: Introductionmentioning
confidence: 99%
“…Attention is one of the most powerful ways we can modulate our own sensory responses to the external world. Many studies have capitalized on this by manipulating selective attention and observing effects on spatiotemporal patterns of cortical activity to otherwise identical stimuli Gau et al, 2020;Guo et al, 2020;Klein et al, 2018). Yet to date nearly all layer-specific studies of attention record exclusively in primary or unimodal cortex, whereas top-down attentional control is thought to originate from high-order areas in prefrontal and parietal cortex (Squire et al, 2013).…”
Section: Attentionmentioning
confidence: 99%